ANALISIS PENGARUH KONTRIBUSI BANK PANIN SYARIAH TERHADAP TOTAL LABA BERSIH BANK PANIN KONVENSIONAL - Masyrifa Zahro (Universitas Islam Negeri Sumatera Utara, 2016)
This research aims to determine The Effect of Contribution Panin Syariah Banking to Total net profit of panin Conventional banking. The sample used in this research is data Net Profit Margin, DPR, Growth Net Income and Asset Growth on Conventional panin Bank's net profit from January 2010 to December 2015. The approach used in this research is a quantitative approach with VAR (Vector Auto Regressive) analysis supported by stationary test, optimal lag test, stability test of VAR model, granger causality test, test impulse response function and variance decomposition test, assisted by Eviews software version 6.From the results of research conducted at alpha 5%, the reaserches conclude that the results of of VAR analysis that Varince Decomposition test showed that NPM variable, DPR, Income Growth, and Growth Assets to Net Income Conventional panin banking In the long term from the beginning to the end of observationiniti net profit has a more dominant influence amounted to 32.76%, by the end of the observation. Meanwhile, NPM variable has an influence on the Bank's net profit amounted to 6.01% Conventional panin Bnking , DPR variable has the effect on 9.81% and increasing of asset amounted to 21, 19%. Granger causality test results showed that all variables had a causal relationship one another, each mean every variable has a two ways relationship with other variables. While the impulse response function test results showed that the net profit Panin Conventional Banking to respon Net Profing Margin (NPM) highly balance, had positive respon, had to the increasing of negative asset, and negative respon of net profit.